(untitled) (Stato, Chiese e pluralismo confessionale, 2023)
Current Law and Religion ABSTRACT: Current Law and Religion, rethought as a subsector of public law having as its object the freedom of the religious dimension of the personality, variously posed - even ir-religious or a-religious -, is able to counter the power of the majorities but also of the totalizing tendency religious minorities. And it facilitates the jurisdiction in seeking a "reasonable accommodation". SOMMARIO: 1. Le fonti non rinnovate - 2. L’affievolimento del dualismo e del bilateralismo - 3. Il diritto ecclesiastico attuale come diritto pubblico delle religioni - 4. Contro le maggioranze ma anche le minoranze di potere - 5. Il confronto con la giurisdizione.